Dry bulk density of Gezira Vertisol as determined by X-ray computed tomography - A. Elias, Eltijani; Rogasik, H; I. Onasch, I. Onasch2; Alaily, F. (المجلة الزراعية; مجلد 1 عدد 2 (2003), 2021)
Soil bulk density is an important parameter indicating the aeration of the soil, the extent of its compaction, its permeability and the state of ease of tillage. It is as well important for expression of gravimetric soil moisture values as volumetric. Current measurements of soil bulk density depend on methods that, to some extent, disturb the soil. In the case of cracking soils, sampling of soil by cylinders probably results in an imprecise determination of the bulk density considering the possible bias in placing the core samplers away from large cracks. The clod method also results in siY1ificant overestimation of the field bulk density of soils because of the small sample used and hence less number of cracks accounted for.      Under continuous cultivation and cropping as practiced in the Gezira for more than 80 years, it is quite possible that the repeated wetting and drying of the soil could cause an adverse effect on soil structure that is possibly envisaged in effects on soil bulk density. X- ray computed tomography is a non-destructive imaging technique to construct a 3-dimensional image of the scanned object (Crestana et al., 1985; Hopmans et al., 1994; Phogat et ale, 1991; Rogasik et al., 1994, 1999). The computed tomogaphy scan has shown so far a consi- derable improvement in quantification of soil morphological parame- ters (Rogasik et al., 1994, 1999).      The objective of this study is to demonstrate the usefulness of the X-ray computed tomography in determination of the narrow spaced differences in the bulk density of cracking soils and to use the results  btained   to   examine   the  effects  of   continuous   cropping   on  soil